Мутагенез, індукований діоксидином в Allium-тесті - Шкарупа, В.М.; Бариляк, І.Р. (Цитология и генетика, 2006)
Изучали влияние разных концентраций диоксидина (ДН) (10–100 мг/л) на цитогенетические параметры клеток апикальной меристемы Allium cepa L. Показан мутагенный эффект ДН в Allium-тесте во всем диапазоне исследуемых концентраций. Определена кривая доза–эффект при концентрациях ДН 10, 20, 30, 40, 50, 100 мг/л. Максимальный мутагенный эффект (43,6 % аберрантных ана-телофаз) выявлен при концентрации 100 мг/л, при этом наблюдали значительное снижение митотического индекса. Показано, что мутагенная эффективность ДН статистически достоверно коррелирует с угнетением митотической активности. The influence of dioxidin in different concentrations (10–100 mg/l) on the cytogenetic parameters of Allium cepa L. has been studied. The mutagenic effect of dioxidin was shown within all the range of the studied concentrations. The curve «dose-effect» has been determined for the concentrations of 10, 20, 30, 40, 50, and 100 mg/l. The peak of the mutagenic effect and significant reduction of the mitotic index were revealed at the concentration of 100 mg/l. It was shown that the mutagenic efficiency of the dioxidin statistically correlated with reduction of the mitotic activities.